2019
DOI: 10.14412/1996-7012-2019-4-55-60
|View full text |Cite
|
Sign up to set email alerts
|

<i>STAT4</i> rs7574865 G/T and <i>IRF5</i> rs2004640 G/T polymorphisms as markers of predisposition to juvenile idiopathic arthritis. What can genetics give to understand its heterogeneity?

Abstract: Juvenile idiopathic arthritis (JIA) is a multifactorial immune-mediated inflammatory disease in childhood, the most common type of rheumatic disease in children. It is characterized by the polygenic type of hereditary predisposition.Objective: to study the association of STAT4 rs7574865 G/T and IRF5 rs2004640 G/T polymorphisms with the predisposition to certain JIA subtypes in the Russian pediatric population.Patients and methods. The investigation enrolled 177 patients, including 66 patients diagnosed with JI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The genetic associations between these two variants and autoimmune diseases, including SLE, RA, Sjogren syndrome and JIA, have been widely reported ( 21 , 51 , 52 ). However, no association between the IRF5 rs2004640 and JIA risk was detected in Russian populations ( 53 ). In the present study, IRF5 rs2004640 and rs10954213 were first found to be significantly related to the susceptibility to JIA in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 96%
“…The genetic associations between these two variants and autoimmune diseases, including SLE, RA, Sjogren syndrome and JIA, have been widely reported ( 21 , 51 , 52 ). However, no association between the IRF5 rs2004640 and JIA risk was detected in Russian populations ( 53 ). In the present study, IRF5 rs2004640 and rs10954213 were first found to be significantly related to the susceptibility to JIA in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 96%